Healthy Smiles Healthy Growth 2004 - Basic Screening Survey of Migrant and Seasonal Farmworker Children in Illinois - Sherri M. Lukes, RDH, MS; Sangeeta Wadhawan, BDS, MPH, Lewis N. Lampiris, DDS, MPH (Blackwell Synergy, 2006)
To obtain baseline data for caries prevalence, use of dental sealants,and dental treatment needs for children of migrant and seasonal farmworkers (MSF Ws) enrolled in the Illinois Summer Migrant €ducation Program, 2004.